Benzopyranones from the Endophytic Fungus Hyalodendriella sp. Ponipodef12 and Their Bioactivities - Ligang Zhou; Youliang Peng; Lingyun Zhong; Liang Xu; Jingfeng Lou; Ziling Mao; Xiangjie Meng; Mingan Wang (Molecules, 2012)
The endophytic fungus Hyalodendriella sp. Ponipodef12 was isolated from the hybrid ‘Neva’ of Populus deltoides Marsh × P. nigra L. In this study, four benzopyranones were isolated from the ethyl acetate extract of Hyalodendriella sp. Ponipodef12, and identified as palmariol B (1), 4-hydroxymellein (2), alternariol 9-methyl ether (3), and botrallin (4) by means of physicochemical and spectroscopic analysis. All the compounds were evaluated for their antibacterial, antifungal, antinematodal and acetylcholinesterase inhibitory activities. 4-Hydroxymellein (2) exhibited stronger antibacterial activity than the other compounds. Palmariol B (1) showed stronger antimicrobial, antinematodal and acetylcholinesterase inhibitory activities than alternariol 9-methyl ether (3) which indicated that the chlorine substitution at position 2 may contribute to its bioactivity. The results indicate the potential of this endophytic fungus as a source of bioactive benzopyranones.